Hepatoprotective Effect of Corm of Ensete ventricosum (Welw.) Cheesman Extract against Isoniazid and Rifampicin Induced Hepatotoxicity in Swiss Albino Mice. (13th August 2021) - Dubiwak, Abebe Dukessa; Damtew, Tesaka Wondimnew; Senbetu, Mengistu Welde; Yewhalaw, Delenasaw; Asere, Tsegaye Girma; Nemo, Gebi; Baye, Minale Fekadie
Abstract : Drug-induced liver injury (DILI) is one of the cumbersome health-related problems which render approximately 50% of liver failure and patients to receiving liver transplantation every year. Antituberculosis drugs such as isoniazid and rifampicin are potentially rendering hepatotoxicity. Ensete ventricosum (Welw.) Cheesman is an herbaceous perennial plant that contributes to the indigenous ethnomedicinal values for the society. This study aimed to investigate the hepatoprotective effect of corm of Ensete ventricosum (Welw.) Cheesman extracts against isoniazid and rifampicin induced hepatotoxicity in Swiss albino mice. The study was conducted on 30 Swiss albino mice randomly allocated into five groups. Group I, group II, group III, group IV, and group V were the groups in which mice were given distilled water, only isoniazid and rifampicin, isoniazid and rifampicin along with 200 mg/kg corm of Ensete ventricosum (Welw.) Cheesman extract, isoniazid and rifampicin along with 400 mg/kg corm of Ensete ventricosum (Welw.) Cheesman extract, and isoniazid and rifampicin along with silymarin per oral per day, respectively. On the 30th day of the experiment, mice were sacrificed after anesthetized, and blood was drawn for the liver function test, and the liver was also taken from each experimental mouse for histopathological evaluation. Data were entered into EpiData version 3.1 subsequently exported to SPSS version 25 for analysis by using one-way ANOVA. Plasma alanine aminotransferase (ALT) levels, aspartate aminotransferase (AST), alkaline phosphatase (ALP), and total bilirubin (TBIL) of group II mice were significantly (p < 0.05 ) elevated as compared to group I. The group of mice treated with a corm of Ensete ventricosum (Welw.) Cheesman at a dose of 400 mg/kg (group IV) and silymarin100 mg/kg (group V) showed a significant (p < 0.05 ) decrease in ALT, AST, ALP, and TBIL as compared to the group II. The liver section of group II showed a change in liver architecture; however, these deformities were not noticed in group IV mice. The result showed corm of Ensete ventricosum (Welw.) Cheesman extract has a very promising hepatoprotective potential against isoniazid and rifampicin induced liver injury.